2020
DOI: 10.1002/jnr.24639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for independent peripheral and central age‐related hearing impairment

Abstract: Deleterious age‐related changes in the central auditory nervous system have been referred to as central age‐related hearing impairment (ARHI) or central presbycusis. Central ARHI is often assumed to be the consequence of peripheral ARHI. However, it is possible that certain aspects of central ARHI are independent from peripheral ARHI. A confirmation of this possibility could lead to significant improvements in current rehabilitation practices. The major difficulty in addressing this issue arises from confoundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In summary, results of our CADP test battery proved differential aging of various parts and functional aspects of the central auditory system. They, in general, provided further evidence for an independent central ARHL component not solely related to peripheral hearing loss, as recently postulated by Bao et al (2020). The more pronounced peripheral hearing loss in the NHE group compared with the HC group made it difficult to attribute the poorer central discrimination performance of the NHE group to aging alone.…”
Section: Discussionsupporting
confidence: 76%
“…In summary, results of our CADP test battery proved differential aging of various parts and functional aspects of the central auditory system. They, in general, provided further evidence for an independent central ARHL component not solely related to peripheral hearing loss, as recently postulated by Bao et al (2020). The more pronounced peripheral hearing loss in the NHE group compared with the HC group made it difficult to attribute the poorer central discrimination performance of the NHE group to aging alone.…”
Section: Discussionsupporting
confidence: 76%
“…These studies found that gap detection ability declined with advancing age independent from peripheral hearing status ( Schneider et al., 1994 ; Snell, 1997 ). Because older listeners display reduced temporal resolution beyond what can be explained by age-related changes to the periphery, gap detection ability is often argued to be a measure of central auditory processes independent of peripheral status ( Bao et al., 2020 ). One main purpose of this study was to examine central versus peripheral contributions to temporal processing using CI users, who could also experience age-related declines in auditory temporal acuity that are seen in older acoustic-hearing individuals.…”
mentioning
confidence: 99%
“…The aging effects on temporal processing (e.g., temporal pulse rate discrimination) are likely to be associated with age-related changes at peripheral (Sergeyenko et al, 2013) and central processing (Anderson et al, 2020;Clinard et al, 2010;Gaskins et al, 2019). However, the relative contributions of those factors are still debated (Bao et al, 2020;Humes et al, 2012). These converging findings regarding age-related changes in temporal processing in CI users may be the result of a common mechanism (Hopkins & Moore, 2011).…”
Section: Effect Of Age On Pulse Rate Discrimination Performancementioning
confidence: 99%
“…Age-related deficits in temporal processing for CI users likely involve both peripheral and central mechanisms. However, their relative contributions are still debated (Bao et al, 2020;Humes et al, 2012). CIs allow us to mostly bypass cochlear effects (e.g., the distortion introduced by damaged or missing inner and outer hair cells, reduced responses due to age-related reductions in the endocochlear potential) and to characterize some of the peripheral contributions with relative ease (Turner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%